PENDIDIKAN ISLAM BERPERSPEKTIF GENDER - Muafiah, Evi (STAIN Pamekasan, 2010)
Abstract: This article describes a map of the causes on gender inequality in the process of education and Islamic education. Authors–by quoting gender expert opinion–proposed a few models attemptting to minimize gender bias through the curriculum such as contributive model, additive model, transformative model and model of social action. It is also presented the learning gender based models that the practitioners of education can select the appropriate models and learning approaches to be applied contextually into the situation by considering the micro and macro conditions surroundding them.